1998
DOI: 10.1016/s0194-5998(98)70122-6
|View full text |Cite
|
Sign up to set email alerts
|

An experimental comparison of different kinds of laryngeal muscle reinnervation

Abstract: In this study, we attempted to determine which method was the best for reinnervating the laryngeal adductor muscles by comparing nerve suture, nerve implantation, and nerve-muscular pedicle (NMP) transfer, as well as the length of time that could elapse after denervation and still allow for successful reinnervation with the ansa cervicalis. Reinnervation was performed in 36 dogs, at 6-, 8-, 10-, 12- and 18-month intervals after denervation via the three methods of muscle reinnervation described above. We noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The first important factor that may have influenced the outcome of surgery is the interval between the phrenic nerve transfer procedure and the onset of bilateral RLN injury. Theoretically, better results of reinnervation surgery are obtained if the interval between the injury and reinnervation is shorter, as is shown both in the literature and in our experimental study [6,30]. We performed the phrenic nerve transfer surgery for some BVFP patients with thyroid surgery-related RLN injury within 6 months after the injury, there are some reasons.…”
Section: Discussionmentioning
confidence: 60%
“…The first important factor that may have influenced the outcome of surgery is the interval between the phrenic nerve transfer procedure and the onset of bilateral RLN injury. Theoretically, better results of reinnervation surgery are obtained if the interval between the injury and reinnervation is shorter, as is shown both in the literature and in our experimental study [6,30]. We performed the phrenic nerve transfer surgery for some BVFP patients with thyroid surgery-related RLN injury within 6 months after the injury, there are some reasons.…”
Section: Discussionmentioning
confidence: 60%
“…The main disadvantage of 1) and 2) is the possibility of laryngeal spasm due to misdirected regeneration of the abductor and adductor fibers. Our previous study demonstrated that nerve implantation, neuromuscular pedicle and neurorrhaphy achieved various degrees of reinnervation, with neurorrhaphy showing the best performance [16]. A single branch of ansa cervicalis was recommended to anastomose with RLN for treating UVFP by Crumley and other investigators [8], [9], [10], [11].…”
Section: Discussionmentioning
confidence: 99%
“…A single branch of ansa cervicalis was recommended to anastomose with RLN for treating UVFP by Crumley and other investigators [8], [9], [10], [11]. However, not all axons of nerve have the regenerative capacity to pass through the anastomosis site; nerve transfer requires a sufficient number of axons to reach the paralyzed laryngeal muscle and produce adequate reinnervation for muscular contraction [16]. Thus, Paniello recommended hypoglossal nerve as a donor nerve for anastomosis to RLN, because it has an advantage over Crumely's procedure, that is the hypoglossal nerve contains more axons than ansa cervicalis [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental results have demonstrated that EMG is useful for evaluating the degree of nerve regeneration ( 34 ), as the amplitude correlates with the number of muscle fibers. If a nerve is injured, some nerve fibers will be unable to transmit the nerve impulse, and the amplitude and latency will be affected ( 35 38 ).…”
Section: Discussionmentioning
confidence: 99%